2013
DOI: 10.1557/opl.2013.361
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure-based Simulations of the High-Strain-Rate Response of Heterogeneous Ti/Al/B Reactive Powder Mixtures

Abstract: We investigate the dynamic behavior under uniaxial stress loading conditions of heterogeneous mixtures of Ti/Al/B via impact simulations on simulated microstructures. We simulate a range of Al concentrations at a constant theoretical material density (TMD) to determine their effects on the mechanical response of a realistic microstructure to impact conditions. We also study particle-level effects such as mixing, extreme deformation, and hot spot formation due to void collapse, as a function of microstructure. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Further details of the powders used in this study can be found elsewhere. 45 Instrumented parallel-plate impact experiments on Ti+2B powders were conducted using the 80 mm helium-driven gas gun. A set of copper capsule fixtures were prepared to contain the powder mixture during the experiments.…”
Section: Shock-compression Of Ti+2b Powder Mixtures: Experiments and mentioning
confidence: 99%
“…Further details of the powders used in this study can be found elsewhere. 45 Instrumented parallel-plate impact experiments on Ti+2B powders were conducted using the 80 mm helium-driven gas gun. A set of copper capsule fixtures were prepared to contain the powder mixture during the experiments.…”
Section: Shock-compression Of Ti+2b Powder Mixtures: Experiments and mentioning
confidence: 99%